A Comparative Study of the Legal History of the Regulation of Excise Tape Attachment in Indonesian and Philippine National Laws - Carl Augustinus Hothinca Soutihon Tampub; Jelly Leviza (Fakultas Hukum Dehasen, 2024)
One of the state revenues comes from excise tax, especially tobacco products, namely cigarettes. However, a breakthrough or certain steps are needed so that state revenue can be obtained optimally. Of course, supervision and control are needed as well as a strict mechanism for the imposition of cigarette excise to ensure the repayment of excise. As a sign of the payment of excise tax, there is currently a physical excise tax band on cigarette products. In addition to Indonesia, it is necessary to look at other countries that regulate cigarette excise tapes as a sign of excise payment, namely the Philippines. We can see this through the mechanisms or legal procedures owned by the country. Therefore, through this research, a Legal Comparative Study of the Legal History of the Regulation of the Placement of Excise Stamps in Indonesian and Philippine National Law will be examined. Then, as a tool to test this scientific paper, it uses a type of juridical-normative research with a legislative approach. In addition, to enrich this research, it will use a comparative law system as a comparison material in processing research data. The result of this research is the hope that based on the mechanisms owned by several countries, Indonesia can follow this pattern as a tangible form of increasing more state revenue.